Investigating the Impact of Quality Management Practices on Quality Performance in Medical Device Manufacturing Industry: An empirical study - Choon Linga, Sim; Shahar Jusoha, Muhammad; Akmar Ishakb, Noormaizatul (International Journal of Engineering and Technology, 2018)
Quality has become a top priority to all manufacturing industries hence recent years had witnessed the growing popularity of quality management practices (QMPs) adoption in developing countries. Nevertheless with the fallen short of QMPs initiatives, a debate into its effectiveness was set in motion. In this regard, this paper aims to empirically re-examine the ambiguity in the relationship between QMPs and quality performance. This paper reveals that QMPs have a significant and positive effect on quality performance in medical device manufacturing (MDM) industry. Furthermore, the findings of this paper shown that QMPs enhances quality performance more effectively when it is introduced in an integrative manner rather than in a piecemeal approach.Â Â